Amide mapping in the human brain using downfield MRSI at 3 T and 7 T - Özdemir, İpek; Etyemez, Semra; Barker, Peter B. (Magnetic resonance in medicine, 2025)
Purpose To quantitatively compare signal‐to‐noise ratios (SNRs), linewidth values, and Cramér‐Rao lower bounds (CRLBs) for amide resonances in the human brain measured at 3T and 7T using downfield MR spectroscopic imaging (DF‐MRSI). Methods Seven normal volunteers (25–52 years, 5 female) were imaged using Philips 3T Elition and 7T Achieva scanners. Both systems have 32‐channel receive head coils and 16‐channel local shim arrays (MRShim GmbH) in addition to high‐order spherical harmonic shims. Three‐dimensional DF‐MRSI data were collected using a previously developed pulse sequence with spectral‐spatial excitation and frequency‐selective refocusing pulses. Matched imaging protocols on both field strengths were applied to achieve a nominal voxel size of 7 × 7 × 15 mm in a scan time of 10.6 min. Spectral analysis was performed using the “LCModel” software package. SNR and CRLB values (%) were compared between 3T and 7T data using univariate general linear models. Results Significantly increased amide SNR and decreased CRLB values (p < 0.05) were found at 7T. Averaged over all brain regions, SNR was 2.9 ± 1.1 at 3T and 5.4 ± 1.5 at 7T, and CRLBs were 11.4 ± 3.9 and 4.9 ± 1.5 respectively. 7T MRI and amide images did show some regional signal dropoff due to transmit B1 inhomogeneity, however. Conclusion Three‐dimensional DF‐MRSI at 7T showed 86% increased SNR and 57% decreased CRLB values compared with 3T, confirming the expected improvements at higher field. Improvements are probably due to multiple factors, including higher magnetization at 7T, the shorter minimum echo time available, among others.